Modeling Stakeholder Interactions in the Oilseeds Sector's Food Security Using a Problem Structuring Approach - sajjad sheikh olia lavasani; Mahmoud Dehghan Nayeri (مدیریت صنعتی)
Objective Food security holds such strategic significance that ensuring it plays a pivotal role in a nation's economic and political self-reliance. The growing reliance on foreign governments for essential food supply considerably undermines a country's political and economic leverage on the global stage. Regrettably, Iran finds itself grappling with over 90 percent dependency on the oilseeds sector, consequently amplifying the nation's susceptibility. Thus, the current study addresses this critical concern, vital for a nation's sustenance. Accordingly, this study comprises the development and cultivation plan of oilseeds in the Islamic Republic of Iran intending to portray a deep-rooted power system that has been formed in the food security system that hinders the optimal implementation strategies. Consequently, the paper aims to provide a model of key stakeholders in the field of food security by employing the Problem Structuring Method (PSM), in search of better analysis of policies and supporting strategies.